The Implementation Of Supervision Management Transformation Based On The Ruangguru Application To Strengthen The Professionality Of Islamic Religious Education Teachers - Budi Setiawan; Agus Salim; Siti Fatimah Siregar; Parida Hanum Siregar; Ramli (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the implementation of the Ruangguru application-based supervision management transformation in strengthening the professionalism of Islamic Religious Education teachers at SMAN 1 Ciomas, Bogor Regency. The study used a qualitative approach with in depth interviews, observation, and document analysis techniques. The results show that the Ruangguru application helps transform conventional supervision into digital supervision that is more efficient, transparent, collaborative, and documented. This transformation strengthens supervision planning, accelerates reporting, facilitates evaluation, and encourages teachers to use supervision data for learning reflection. The main impact is seen in improving discipline, digital competence, accountability, and collaboration between teachers. Obstacles found include limited digital literacy, internet access, device readiness, and adaptation to the new system. This study concludes that Ruangguru-based supervision can be a model for professional development of Islamic Religious Education teachers that is adaptive, data-driven, and relevant to the needs of Islamic education in the digital era, especially in improving the quality of learning, reflective culture, and sustainable school supervision governance at the public secondary education level.